1964
DOI: 10.1097/00004032-196412000-00024
|View full text |Cite
|
Sign up to set email alerts
|

95Zr-95Nb in Human Lungs from Fallout

Abstract: The presence of easily measurable quantities of intermediate-lived fission products in ground level air during the first half of 1963 prompted an investigation of the distribution of gamma emitting nuclides in human lungs. Lungs from five cadavers were dissected, ashed and measured for 95Zr-95Nb, 13'Cs and 40K using a 4 x 4411. NaI well crystal and a multichannel analyzer. Prior measurement of the cadavers in a whole body counter using a 8 x 4-in.NaI crystal positioned over their backs, permitted calibration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

1968
1968
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 1 publication
0
7
0
1
Order By: Relevance
“…65 Tagen (Cofield 1963;Wrenn et al 1964). Die Halbwertszeit, bezogen auf die Gesamtkörperspeicherung, beträgt beim BeagleHund 328-365 Tage (Waligora 1971).…”
Section: Verteilung Ausscheidungunclassified
“…65 Tagen (Cofield 1963;Wrenn et al 1964). Die Halbwertszeit, bezogen auf die Gesamtkörperspeicherung, beträgt beim BeagleHund 328-365 Tage (Waligora 1971).…”
Section: Verteilung Ausscheidungunclassified
“…Wrenn et al (28) have shown that during periods of weapons testing, 95 Zr and its radioactive daughter, 95 Nb are present in human lungs and can be measured in vivo using a sodium iodide crystal positioned directly in contact with the chest. In New York City, where their measurements were made, Wrenn and his associates found that the dose to the lungs was about 3 μ-rad/day from this pair of isotopes.…”
Section: Nuclear Weaponsmentioning
confidence: 99%
“…Previous studies of fallout 9sZr-95Nb in ZNbm , 93 Nb", "b, %Nb", 95Nb and 95Nbm are humans have shown most of the radioactivity to be contained in the lungs (Ru62;Ru65;Os63;Wr64;Du66). This indicates that ifihalation was the major exposure route.…”
Section: Introductionmentioning
confidence: 96%
“…Niobium-95 is also the daughter product of radioactive 95Zr decay. Since both of these isotopes are abundant fission products, they are commonly found together in particulate material released from fission processes (Har64; Wr64;Du66). Radioactive decay of 95Nb occurs by beta emission Niobium metal is a very refractory material and has been suggested for use in structural components of fusion reactor systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation